Pendampingan Publikasi Ilmiah sebagai Pengembangan Keprofesian Berkelanjutan Guru SMK di Surakarta - Estriyanto, Yuyun; Saputra, Taufik Wisnu; Towip, Towip; Widiastuti, Indah (FKIP Universitas Sebelas Maret, 2023)
Continuing Professional Development (CPD) for teachers includes self-development activities, scientific publications, and innovative works. Scientific publications are often an obstacle to a teacher's career. Therefore, the skill of writing a scientific paper is a competency that must be possessed by teachers. This community service aims to provide assistance and improve scientific writing skills for Vocational High School (SMK) teachers. The method used consists of a classical approach of holding workshops and individual post-workshop assistance until submitting participant articles to scientific journals. Based on the results of the program, it was found that: (1) the teachers showed high enthusiasm in participating in the program; (2) there is one participant who successfully published his article in the Indonesian Sinta indexed journals; (3) participants who are still in the process and who have already had draft articles still need individual assistance until they can publish into scientific journals. The mentoring program is still needed on an ongoing basis so that writing culture is formed as a part of the CPD program.